Genetic Polymorphisms in Enzymes Involved in One-Carbon Metabolism and Anti-epileptic Drug Monotherapy on Homocysteine Metabolism in Patients With Epilepsy - Zhu, Shaofang; Ni, Guanzhong; Sui, Lisen; Zhao, Yiran; Zhang, Xiaoxu; Dai, Qilin; Chen, Aohan; Lin, Wanrong; Li, Yinchao; Huang, Min; Zhou, Liemin (Frontiers in Neurology, 2021)
Abstract Aims: To investigate the effects of single nucleotide polymorphisms (SNPs) in genes of one-carbon metabolism (OCM) related enzymes and anti-epileptic drug (AED) monotherapy on homocysteine (Hcy) metabolism in patients with epilepsy, and to further explore specific SNPs that may increase patients’ susceptibility to the effects of AEDs on the Hcy imbalance. Method: This case-control study analyzed 279 patients with epilepsy, including patients receiving monotherapy with valproate (VPA) ( n = 53), oxcarbazepine (OXC) ( n = 71), lamotrigine (LTG) ( n = 55), or levetiracetam (LEV) ( n = 35) and patients who had not taken any AEDs (controls, n = 65) for at least 6 months. Serum levels of vitamin B12 (vit B12), folate (FA) and Hcy were measured, and 23 SNPs in 13 genes of OCM-related enzymes were genotyped in all patients. Results: Methylenetetrahydrofolate reductase (MTHFR) rs1801133 was associated with elevated serum Hcy levels in patients with epilepsy (P < 0.001), and patients presenting the TT genotype exhibited higher serum Hcy levels than patients with the CC (P < 0.001) or CT (P < 0.001) genotype. A subsequent multiple linear regression analysis showed that AED monotherapy with VPA (vs. control: P = 0.023) or OXC (vs. control: P = 0.041), and genotypes of MTHFR rs1801133 TT (vs. CC: P < 0.001; vs. CT: P < 0.001), transcobalamin 2 (TCN2) rs1801198 CC (vs. GC: P = 0.039) and folate receptor 1 (FOLR1) rs2071010 AA (vs. GA: P = 0.031) were independent risk factors for higher Hcy levels. In the subgroup analysis of patients taking OXC, we found that patients with genotypes of MTHFR rs1801133 TT (vs. CC: P = 0.001; vs. CT: P < 0.001) and TCN2 rs1801198 CC (vs. GC: P = 0.021; vs. GG: P = 0.018) exhibited higher serum Hcy levels. Conclusions: VPA, OXC, and genotypes of MTHFR rs1801133 TT, TCN2 rs1801198 CC and FOLR1 rs2071010 AA are all independent risk factors for elevated Hcy levels in patients with epilepsy. Moreover, genotypes of MTHFR rs1801133 TT and TCN2 rs1801198 CC may increase patients’ susceptibility to the effect of OXC on disrupting Hcy homeostasis.